Modeling and simulations of drug distribution in the human vitreous - Dörsam, Simon; Friedmann, Elfriede; Stein, Judith (Conference "Topical Problems of Fluid Mechanics 2017", 2017)
We develop a mathematical model for the drug distribution in the vitreous body of a human eye. The drug is injected in the vitreous and used for the treatment of retinal diseases. For an optimal ffect the drug is supposed to stay as long as possible in a certain area. We model the distribution of the drug with anisotropic diffusion which include the effect of the collagen fibers which have a certain orientation in the vitreous body. In addition to the diffusion we include also the steady permeating ow of the aqueous humor and model it with the Darcy equation driven by a pressure drop. The simulations are performed with the Finite Element method.
Gesehen am 17.09.2018